The development of the information management research area - Elena Maceviciute; T.D. Wilson (Information Research: An International Electronic Journal)
In the 1980s information management was emergent and perceived by some to be simply a re-write of traditional librarianship. However, it has continued to thrive and much of what is now included is far removed even from modern information science, although information management draws upon ideas from both librarianship and information science. In one form or another it is likely to persist in the future, since information problems are likely to persist in organisations. The means for resolving the problems may change, but the need to understand those problems and develop solutions will remain.